Analyzing the Impact of BTS on Resolving the Problem of Youth Mental Health - Sihombing, Lambok Hermanto (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
This Journal outlines the efforts of BTS as a K-pop boy group to help to resolve the problem of Youth Mental Health, in which Korea itself has a background as one of the countries with the most mental health cases in the world. More deeply, in this study, the writer conducted an analysis of several forms of BTS activities that show their efforts in reducing mental health problems, in this case including; song lyrics in the BTS album, the social campaign they run with UNICEF, "Love Myself", and finally the public response to these BTS efforts. And in the results of this research, it can be seen that BTS does indeed have a positive impact through their songs lyrics and social campaigns. This can be seen from the response of the public who claimed to feel "healed", found motivation, and also forgot their problem after listening to BTS songs. In addition, in social media, it can also be seen how with the #BTSLoveMyself campaign, the users of this hashtag also provide support to fellow people with mental health problems.